Antibacterial activities of Ligaria cuneifolia and Jodina rhombifolia leaf extracts against phytopathogenic and clinical bacteria - Soberon, Jose Rodolfo (2014)
Six plant extracts prepared from Ligaria cuneifolia and Jodina rhombifolia were screened for their potential antimicrobial activities against phytopathogens and clinically standard reference bacterial strains. Bioautography and broth microdilution methods were used to study samples antibacterial activities against 7 bacterial strains. The minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of samples were attained. An antibacterial activity guided isolation and identification of active compounds was carried out for L. cuneifolia methanolic extract (LCME). Both methanolic and aqueous extracts from L. cuneifolia showed inhibitory activities against phytopathogenic bacteria, with MICs ranging from 2.5 to 156 μg mL−1 for LCME and 5 mg mL−1 for the aqueous extract. None of the three J. rhombifolia extracts showed significant antibacterial activities against phytopathogenic strains (MIC > 5 mg mL−1), except for the aqueous extracts against Pseudomonas syringae (MIC = 312 μg mL−1). Only LCME showed bactericidal activities against phytopathogenic strains (MBCs = 78 μg mL−1). The LCME exhibited significant inhibitory activity against reference clinical strains: Escherichia coli (MIC = 156 μg mL−1) and Staphylococcus aureus (MIC = 78 μg mL−1, MBC = 312 μg mL−1). LCME active compounds were identified as flavonol mono and diglycosides, and gallic acid. The antibacterial activity of purified compounds was also evaluated. A synergistic effect against S. aureus was found between gallic acid and a quercetin glycoside. Hence, anti-phytopathogenic bacteria potential compounds isolated from L. cuneifolia could be used as an effective source against bacterial diseases in plants.